Reducing Coil Break Rejection At Hot Skin Pass Mill PT Krakatau Steel - Mardiana, Dicky; Basri, Mursyid Hasan (The Indonesian Journal of Business Administration, 2013)
Coil break rejection at Hot Skin Pass Mill PT Krakatau Steel is a repetitive claim from consumer and target of quality objective is still out of target. Coil break is surface defect of hot rolled coil with appearance of surface looks some areas of small lines transverse to rolling direction, low contrast to surface white or black lines. Lower yielding point of the hot rolled coil tends to have coil break rejection. Hot Skin Pass Mill (HSPM) is dedicated to prevent coil break. Anti Coil Break is the equipment at the entry section of HSPM which has main function to prevent coil break. If this equipment works properly then coil break rejection on the surface of strip can be prevented. Engineering, operation, and organization category can influence the rejection. Engineering : Anti Coil Break parameter, inspection of equipment, and quality of strip inspection. Operation: Adjustment of Finishing Temperature-Coiling Temperature and operation parameter HSPM. Organization : Span of control too wide and organization alignment. Each factor will be analyzed by Root cause analysis find the root of problem. Each category of engineering, operation, and organization will be analyzed to recommend as implementation plan. Alternative solutions proposed are : improvement of equipment reliability, redesign Anti Coil Break Roll, implementation of Statistical Process Control, review Quality Product Level, empowerment of structures, and alignment of organization. Each alternative was evaluated to propose as implementation plan. Implementation plan consists of the mandatory plan or the highest priority of each category.Â Keywords : coil break, PT Krakatau Steel, hot rolled coil, yielding point, finishing temperature, coiling temperature.